PENGEMBANGAN BUKU AJAR BAHASA INDONESIA BERMUATAN NILAI-NILAI KARAKTER MENGGUNAKAN MODEL PEMBELAJARAN BERBASIS MASALAH - Iva Mursida (EDU-KATA, 2019)
The purpose of this research is to know the process development of teaching materials using a four- D model of development and to determine the quality of the development of teaching materials Indonesian containing character values ​​using problem-based learning model . Quality development consists of the validity , effectivity, and practicality.. In this research and development resulting product in the form of teaching materials Indonesian containing character values ​​using problem-based learning model . The process of development of teaching materials used four- D model of development that has 4 ( four ) steps of the process , namely 1. Define, 2. Design , 3. Develop, 4. Dessiminite. Data quality development in the form of data validity, effectivity,and practicality.The results of this study contains development process and data quality development . At the level of validity , obtaining a total score of 90.5 % . At the level of practicality , obtain excellent results by keterlaksanaan RPP 88%, the student response 87 % , 88 % .In response rate teacher effectiveness , student activities earn a score of 85 % and activities for teachers to get a score of 80 %.